Upaya Meningkatkan Hasil Belajar IPS dengan Menggunakan Metode Pembelajaran Practice Rehearsal Pairs Berbantu Media Audio Visual Pada Peserta Didik Kelas IV SDN-1 Kasongan Lama Tahun Pelajaran 2016/2017 - Muhammad Tarki; Suniati Suniati (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to: (1) find out the learning activities of students in social studies learning especially in the economy of a society with the method of determining possible pairs assisted by audio-visual media in fourth-grade students of the Kasongan Lama Elementary School. (2) To find out whether or not there is an increase in social studies learning outcomes on the economic aspects of the community with the method of practice rehearsal pairs assisted by audio-visual media in fourth-grade students of the Kasongan Lama Elementary School. This study uses the class action research method (CAR).